Relationship Strategy Family Coping With Quality Of Life In Elderly Post Stroke - Limansyah, Dodik; Sahar, Junaiti; Sukihananto, Sukihananto (STIKes Surya Mitra Husada, 2018)
Background: Stroke is the highest cause of death in urban areas, one of the regions in Indonesia with stroke exceeds the national rate is the city of Pontianak. Purpose : This study aims to determine the relationship of family coping strategies to the quality of life of elderly post-stroke in the city of Pontianak. Methods : Analytical research design correlation with cross sectional approach. sampling in total sampling with respondents amounted to 58 respondents. The sample of this study was post-stroke elderly and family members as caregiver or primary outpatient who treated elderly with post stroke. Result : The results of multiple linear regression analysis or anova test (f test) with p value = 0.001 (<0.05) indicating that there is a significant relationship between social support, reframing, seeking and receiving, passive income and income with the quality of life of the elderly post stroke. Conclusion : Social support is a dominant element of coping strategy. The role of community nurses is needed to support family caregivers in providing social support to post-stroke elderly.